A look at the link between bio-altruistic values and pro-environmental attitude in university students - Ayay-Arista, Guido; Gustavo Estrada-Araoz, Edwin; Juan Ramirez Herrera, Mauro; Chávez Santos, River; Antonio Malca Florindes, Jorge; Walter Coronel Chugden, José; Alberto Pecho Tataje, Luis; Carranza Guevara, Rosas (Heritage and Sustainable Development, 2024)
The growing environmental concern has highlighted the need to adopt pro-environmental behaviors. Despite previous research on the relationship between environmental values and attitudes, the connection between bio-altruistic values and pro-environmental attitudes in university students remains to be explored. The general objective of this study was to analyze the link between bio-altruistic values and pro-environmental attitudes in university students, and the specific objectives were to evaluate the levels of these variables in different dimensions. Using a correlational design, the New Ecological Paradigm Scale (NEP) and the Multiple Motives for Environmental Protection Scale (MEPS) were administered to 706 students from three public universities in northern Peru. The results revealed that 90.5% of the students exhibited "Good" levels of bio-altruistic values, and the majority showed positive pro-environmental attitudes. The research evidenced a significant association between bio-altruistic values and pro-environmental attitudes, suggesting that as bio-altruistic values increase, pro-environmental attitudes tend to be more positive toward the environment. These findings support previous research, highlighting the positive influence of bio-altruistic values on pro-environmental attitudes. The importance of educational and psychological factors is highlighted, underscoring the need for educational strategies to foster bio-altruistic values. It is concluded that cultivating these values in students can be crucial to promoting pro-environmental behavior and attitudes and advocating their inclusion in educational programs and public policies to build a more sustainable society.